Toxic cyanobacterial blooms in a Pampean shallow lake: An approach to their ecology from morpho-physiological traits - Cocciolo, Fiorella Tatiana (2021)
This study presents the ecological characterization of the assemblage of bloom forming cyanobacteria from laguna Salada de Monasterio (SM), Buenos Aires. The relationships between abundance, biomass and morphology of the species with the environmental conditions in the shallow-lake along two warm periods are assessed. SM was seriously impaired by toxic cyanobacterial blooms dominated by Raphidiopsis mediterranea, which in the first stage was accompanied by Planktothrix agardhii, Anabaenopsis cf. circularis, A. cunningtonii and Cuspidothrix issatschenkoi, and by C. issatschenkoi in the second period. Total abundance and biovolume of both periods were positively correlated, and a lower density of cyanobacteria was registered in the second period, with a higher water level. The alert level 2 for drinking water and the guide level 2 for recreational waters (World Health Organization, WHO), in terms of the abundance of cyanobacteria cells, were exceeded at both warm periods. The morphological differences observed among species were associated with responses to light availability in the water column. R. mediterranea presented a direct association between filament length and width that favoured its development, even in scenarios with high turbidity and light limitation, where the other species were not found. Dissolved organic nitrogen (NOD) is considered the preferred nitrogen source due to its high concentration (average: 3.76 mg/L). A low frequency of akinetes was found for Anabaenopsis and C. issatschenkoi, indicating a favorable scenario for their development. Microcystin (-LR and-YR) was registered in the first period with concentrations exceeding 1µg/L (WHO guidance level), with P. agardhii and Anabaenopsis being the potential toxin producers; saxitoxin was not detected.